Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1108/ijrdm-07-2015-0094
|View full text |Cite
|
Sign up to set email alerts
|

Facility location for a closed-loop distribution network: a hybrid approach

Abstract: Purpose The purpose of this paper is to find a sustainable facility location solution for a closed-loop distribution network in the uncertain environment created by of high levels of product returns from online retailing coupled with growing pressure to reduce carbon emissions. Design/methodology/approach A case study approach attempts to optimize the distribution centre (DC) location decision for single and double hub scenarios. A hybrid approach combining centre of gravity and mixed integer programming is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
0
11
0
1
Order By: Relevance
“…Then, for the 232 different references, it was possible to identify 206 authors, the most cited were presented in the graph illustrated in figure 8. For these authors, the presence of their works in the publications of this content analysis was validated, so that the publications with the highest recurrence of the same authors were in the publications of Ghadge et al (2016) and Lamba et al (2019), as shown in Table 5. In that order, for the 236 references used in the 7 selected publications, 324 citations were identified.…”
Section: The Identification Of Researches Applied To E-commercementioning
confidence: 99%
See 2 more Smart Citations
“…Then, for the 232 different references, it was possible to identify 206 authors, the most cited were presented in the graph illustrated in figure 8. For these authors, the presence of their works in the publications of this content analysis was validated, so that the publications with the highest recurrence of the same authors were in the publications of Ghadge et al (2016) and Lamba et al (2019), as shown in Table 5. In that order, for the 236 references used in the 7 selected publications, 324 citations were identified.…”
Section: The Identification Of Researches Applied To E-commercementioning
confidence: 99%
“…Meanwhile, Ghadge et al (2016) adapted known techniques (COG/MILP) to contemplate the reverse flow and optimized the result minimizing transportation costs, handle operations, and consequently atmospheric emissions in the allocation of facilities. However, the model did not consider remanufacturing and disposal operations for returned products, so additional studies would be necessary for real applications including such activities.…”
Section: The Identification Of Researches Applied To E-commercementioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [7] made a research for the selection of locations for the facilities which may have the minimum cost and maximum demand/coverage areas and which may become unserviceable due to natural disasters or other events. Ghadge et al [8] attempted to optimize, via the case study, the decision of single and double center distribution center location. Elevli [9] applied F-PROMETHEE for selecting one of the five logistics center locations in Samsun-Turkey while taking into account the position, property price, geographical characteristics, ownership, and property conditions as criteria.…”
Section: Literature Researchmentioning
confidence: 99%
“… Afshari et al, 2016 ; Aydin, 2020 ; Ayvaz et al, 2015 ; Bertsimas and Sim, 2004 ; Chakraborty et al, 2018 ; De Rosa et al, 2013 ; Demirel et al, 2016 ; Doan et al, 2018 ; Fang et al, 2011 ; Feitó-Cespón et al, 2017 ; Ghadge et al, 2016 ; Gu and Gao, 2012 ; Hamdan and Diabat, 2020 ; Hamidieh et al, 2017 ; Hatefi and Jolai, 2014 ; Hatefi et al, 2015 ; Hatefi et al, 2016 ; Heydari and Ghasemi, 2018 ; Heydari et al, 2018 ; Hosseini-Motlagh et al, 2019 ; Hosseini-Motlagh et al, 2020 ; Hosseini and Sarder, 2019 ; Hosseini and Ivanov, 2019 ; Hosseini et al, 2019a ; Hosseini et al, 2019b ; Ivanov et al, 2014a ; Ivanov et al, 2014b ; Ivanov et al, 2016 ; Ivanov et al, 2017 ; Jabbarzadeh et al, 2014 ; Jain et al, 2017 ; John et al, 2018 ; Kinra et al, 2019 ; Liao, 2018 ; Mohapatra et al, 2019 ; Niknejad and Petrovic, 2014 ; Pavlov et al, 2019 ; Pishvaee et al, 2011 ; Phuc et al, 2017 ; Qiaolun and Tiegang, 2012 ; Qiaolun and Tiegang, 2013 ; Ren et al, 2020 ; Sawik, 2017 ; Setak et al, 2019 ; Shuang et al, 2019 ; Suryawanshi and Dutta, 2019 ; Tosarkani and Amin, 2019 ; Tucker et al, 2020 ; Yu and Solvang, 2017 ; Zhang et al, 2018 ; Zhao et al, 2018 .…”
Section: Uncited Referencesunclassified